(untitled) (PANGEEA, 2025)
Teaching geography in the class, in a formal way, is a normal thing to do. Teaching geography in a non-formal context, from time to time, is different, seems a bit strange and needs courage to even think about it. In fact, it is not so difficult, it requires a good plan ahead and desire to make students understand how important it is to actually see and do things outside in the open. This paper presents my experience in taking the 9th grade students outside the classroom and presenting aspects from three different topics: the Universe (at the National Observatory), glacial and river erosion (on a trip on the Transfagarasan road) and atmosphere (at the National Meteorological Administration). All in all, the students were enthusiastic about this mixing of theory and practice and I am sure they will better remember Cumulus clouds and forms of erosion as part of their personal experience.